ASENTAMIENTOS CHACHAPOYA EN EL NORTE DE LA PROVINCIA DE LUYA, DEPARTAMENTO DE AMAZONAS - Koschmieder, Klaus (2014)
The archaeological culture known as the Chachapoya developed between 800 and 1470 AD in the northeastern highlands of Perú. In the province of Luya, as in most of the Chachapoya territory, residential settlements (llaqtas) are located on hilltops (Chichita) and less often at the base of cliffs. Other sites, located on the slopes of mountains, were occupied temporarily, mainly for agricultural activities (Pullía) or ceremonial matters (Kacta). At first glance, the architectural features appear to be uniform, with a predominance of circular or oval stone buildings originally covered with conical roofs made of timber and straw. However, new studies show peculiarities in the configuration of the interior space of the buildings and the decoration of the exterior walls with geometric or figurative friezes. We attribute these distinctive features to the presence of different Chachapoya groups and to the diversity of activities that took place in the circular environs of the llaqtas. The results of the present study have significant implications for the interpretation of the function of the Kuelap complex, which was not a fortress nor a typical population center. Rather it was the most important administrative and ceremonial center in the northern territory of the Chachapoya.